FIBER REINFORCED POLYMER AS A REINFORCING MATERIAL FOR CONCRETE STRUCTURES - Samuel Layang (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
Concrete is one of the materials that is widely used in various structural works because it has advantages, especially it has high compressive strength and is easy to form. However, concrete can also be damaged by physical, chemical, mechanical and excessive loads. Damaged concrete structures must be repaired and strengthened immediately to prevent further damage that can lead to structural failure. One of the materials that can be used for structural reinforcement is Fiber Reinforced Polymer (FRP). FRP is a composite material made of three basic components, namely fiber, polymer and additives. FRP has advantages such as having high strength, light weight, corrosion resistance, easy installation, requiring little or no scaffolding. FRP is very well used to increase the capacity of structures in buildings that are undergoing changes in function